Regulation of health care professionals as a quality strategy. (13th November 2019) - Panteli, D; Kreutzberg, A; Reichebner, C; Maier, C; Destrebecq, F
Abstract: Health professionals are both a health system input and an active component of the functions that the health system performs. As such, the performance of the health workforce is directly linked to the quality of health services. Regulation is essential to define a clear framework within which health professionals acquire and maintain the competence needed to provide health services that are of high quality, i.e. that are safe, effective and patient-centered. This presentation discusses the evidence on a sequence of strategies that regulate health professionals, looking at how they are currently deployed in Europe, how (cost-)effective they are, and what can be done to optimize their implementation. Adopting a comprehensive perspective ranging from the entry into training to life-long maintenance and demonstration of competence, the presentation brings together a) strategies to develop professional competence (including training structure and contents, curriculum development and the accreditation of institutions for health education); b) strategies that regulate the entry of physicians and nurses into their professions (e.g. licensing and registration); c) mechanisms to maintain competence (e.g. continuing professional development); and d) levers to address instances when fitness to practice comes into question.